Clinical efficacy of nanohydroxyapatite-containing toothpaste at relieving dentin hypersensitivity: an 8 weeks randomized control trial - Bennett Tochukwu Amaechi; Kelly C. Lemke; Shyamali Saha; Minh N. Luong; Jonathan Gelfond (Nature Publishing Group, 2021)
Abstract Objective The objective of this study was to investigate and compare the effectiveness of several toothpastes containing nanohydroxyapatite (nano-HAP) to relieve dentin hypersensitivity (DHS) with that of a commercial desensitizing dentifrice containing calcium sodium phosphosilicate (CSPS). Materials and methods In this double-blind, randomized, parallel-group clinical trial, patients diagnosed with DHS and qualified to participate were randomized into four groups: toothpaste containing 10% nano-HAP (10%nano-HAP), 15% nano-HAP (15%nano-HAP), 10% nano-HAP supplemented with potassium nitrate (KNO3) (10%nano-HAPKN), or CSPS. Subjects' baseline and post-treatment sensitivities were assessed using visual analog scale (VAS) after the application of ice-cold and air stimuli. Subjects used their assigned toothpaste for routine toothbrushing twice daily. Post-treatment sensitivity was assessed every 2 or 8 weeks. Mean change in VAS (mm) from baseline at each time point were compared using random-intercept, mixed-model analysis and Duncan test (P < 0.05). Results With either air or cold stimulus, VAS indicated a significant (P < 0.001) reduction from baseline DHS at each time point with all test toothpastes. Among the nano-HAP toothpastes, 15%nano-HAP and 10%nano-HAPKN were consistent in DHS reduction with both stimuli. With either stimuli, the CSPS did not significantly differ from 15%nano-HAP and 10%nano-HAPKN at any time point. Conclusions Toothpaste containing nano-HAP (10 or 15%) alone or supplemented with KNO3 was as effective as CSPS for relief of DHS symptoms when used at least twice daily.